Determinants of banks’ costumer’s intention to adopt internet banking services in Yemen: using the Unified Theory of Acceptance and Use of Technology (UTAUT) - Al-Fahim, Nabil Hussein (Institute of Electrical and Electronics Engineers Inc., 2021)
Researches on Internet Banking (IB) in the context of Yemen is still lacking which creates the necessity to conduct such a study to investigate the adoption level of IB services. Thus, this study aims at examining and investigating the factors influencing the adoption of IB among banks’ customers in Yemen through the use of the UTAUT theory. The framework of this study comprises one endogenous variable the intentions to use IB services) and five exogenous variables in which the exogenous variables consist of effort expectancy, performance expectancy, trust, social influence, and awareness. The identified moderators in this study are the role of age and experience that influence the intentions of banks’ customers to use and adopt IB services. The survey questionnaire was distributed to a sample that consists of 354 bank customers and the returned data was screened and then analyzed using structural equation modeling (SEM) to investigate the correlations and relationship among variables. Meanwhile, the indirect impact of the moderating variables was investigated using multiple-group analysis (MGA). The results of this study revealed that effort expectancy, performance expectancy, awareness, and trust have a significantly positive impact on customers’ intention to adopt IB services in Yemen. However, the social influence showed no significant effect on IB services. Moreover, the age and experience variables showed a moderating impact on customers’ intention to adopt IB services in Yemen.